Stimulasi Kecerdasan Musikal Anak Usia Dini Melalui Kegiatan Bernyanyi TerencanaPada Kelompok B RA Al-Amin 3 Cemani - Anita Wardhani; Nurul ‘Aini Muthmainnah; Alfaein Nisa Nur Salamah; Rizky Amalia Muflihah; Wahyu Widayanti (Diksi: Jurnal Pendidikan dan Literasi, 2026)
Musical intelligence is an important aspect of child development that needs to be stimulated from an early age because music plays a significant role in supporting children's cognitive, emotional, and social development. This study aims to describe the implementation of singing activities as an effort to develop musical intelligence among Group B children at RA/TK Al Amin 3 Cemani. The study employed a descriptive qualitative approach involving 20 children aged 5-6 years, 2 teachers, and 1 principal as research subjects. Data were collected through observation, interviews, and documentation, while data analysis used the interactive model of Miles, Huberman, and Saldana. The findings revealed that singing activities designed and implemented in a structured and systematic manner had a positive impact on the development of children's musical intelligence, as reflected in their ability to recognise tones (85%), follow rhythms (90%), and express themselves through singing (80%). Variations of singing activities combined with body movements, the use of simple musical instruments, and thematic songs created an active, creative, and enjoyable learning environment for children. Therefore, singing activities can serve as an effective and meaningful learning strategy in optimally developing the musical intelligence of Group B children while providing learning experiences that are aligned with the characteristics of early childhood development